Case report: severe cytomegalovirus primary infection in an immunocompetent adult with disseminated intravascular coagulation treated with valganciclovir. Issue 1 (December 2015) - Müller, Niklas; Schampera, Matthias; Jahn, Gerhard; Malek, Nisar; Berg, Christoph; Hamprecht, Klaus
Abstract Background Disseminated intravascular coagulation (DIC) is a very rare complication of disseminated cytomegalovirus (CMV) infection. So far it is mainly described for immunocompromised patients. Case presentation A 49-year-old immunocompetent Caucasian male presented with sudden onset of fever and DIC due to primary CMV infection, which was treated with Valganciclovir. CMV-specific IgG-avidity and epithelial cell-specific neutralisation-capacity developed five weeks after onset of symptoms. We describe the first case of an immunocompetent patient suffering from DIC due to a CMV primary infection successfully treated with Valganciclovir. Conclusions Primary CMV infection can occur accompanied with life threatening complications even in immunocompetent patients. Immediate treatment with Valganciclovir should be considered as an early treatment of choice in severe cases since specific neutralisation capacity might need several weeks to develop.